Analysis of the features of foreign language teaching using ICT during the pandemic restrictions - Mariyat Aslanovna Tlevtsezheva (Вестник Майкопского государственного технологического университета)
The modern labor market, focused on the level of the technological progress, makes a set of requirements for university graduates, which are based on fluency in a foreign language. The protracted period of the pandemic forced to transfer the educational process in universities to an online format, for which the entire existing potential of e-learning of universities was used (electronic information and educational environment + modern information and communication technologies + competencies of teachers). But the question is whether the employer will be satisfied with the results of teaching young specialists a foreign language through ICT alone. The article makes an attempt to analyze the positive and negative aspects of teaching a foreign language, exclusively using the electronic information and educational environment of an organization. The research methodology and methods. The source base of the study are scientific and journalistic articles on the topic, information from the official website of the Ministry of Science and Higher Education of the Russian Federation “Portal of Federal State Educational Standards”. In the research the methods of structural analysis, synthesis, comparison, generalization were used.